Chinese Agricultural Reform the WTO and FTA Negotiations - Shunli Yao (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2006)
China's early industrialization created distortions.This paper identifies major distortions in the Chinese economy in the pre-reform era and brings agricultural distortions into perspective.
Keywords: F1; 330; Agricultural Reform; China; Liberalization; WTO; FTA